Two-dimensional and serial column reversed-phase separation of phenolic antioxidants on octadecyl-, polyethyleneglycol-, and pentafluorophenylpropyl-silica columns - Bláhová, Eva; Jandera, Pavel; Cacciola, Francesco; Mondello, Luigi (Journal of separation science, 2006)
The separation selectivity of octadecyl-silica (C18) and of bonded pentafluorophenylpropyl-silica (F5) and PEG-silica columns was compared for natural phenolic antioxidants. The separation selectivities for phenolic antioxidants on C18 and F5 columns are strongly correlated, but low selectivity correlation indicating strong differences in the retention mechanism was observed between the C18 and PEG columns. Hence, the combination of a C18 and a PEG column is useful for separation of phenolic antioxidants that are not fully separated on single columns. Two-dimensional comprehensive liquid chromatography using a short PEG-silica column in the first dimension and a conventional C18-silica in the second dimension has the advantage of on-column focusing of the fractions transferred onto the C18 column in the second dimension, as a weaker mobile phase is used in the first dimension than in the second dimension. However, a stop-flow set-up in the first dimension system is necessary after the transfer of each fraction to the second dimension. Peak capacity is considerably larger but the separation time is much longer than with serially coupled PEG and C18 columns, which were employed for separation of beer and hop extract samples in connection with coulometric detection.
Keywords: oxid křemičitý; rostlinné extrakty; fenoly; financování organizované; Phenols; vysokoúčinná kapalinová chromatografie; Plant Extracts; polyethylenglykoly; Polyethylene Glycols; Financing, Organized; lidé; Antioxidants; Chromatography, High Pressure Liquid; Silicon Dioxide; antioxidancia; Humans